Employment experience of immigrant workers in tourism - Žigo, Alja (Academica turistica, 2017)
This research explores the experience of immigrants employed in tourism in Slove- nia. Four main areas were studied: (1) formal regulation of working and living, (2) health and social care, (3) job satisfaction, and (4) integrationinto the Slovenianen- vironment. The causes for this research were recent stories in various media regard- ingforeignworkersinSlovenianeconomyandlittletonoresearchstudiesinthefield of tourism. The idea of the article was to demonstratethe employment of labour mi- grants% experiences in tourism and to make proposals to improve the employment experience in the future. We started out by studying the existing theory, and then performed qualitative research, in which the employment experiences of four im- migrants was studied in the previously mentioned four identified areas. Interviews were carried out with immigrants from different countries and of different profes- sions,andwerelaterevaluatedwithcontentanalysis.Theresultsofthestudyshow that the employment experience of immigrants employed in tourism in Slovenia is both positive and negative, as there were positive and negative factors of experience identifiedin all areasof research.We do notwantto give a generalisedassessmentof theexperience,but rathershow certainviewsandexperiences;basedonthat,wecan learn.Theresultsdonotapplytotheentirepopulation,butwiththemwepresentthe diversity of the subject. The greatestlimitation while researchingwas finding partic- ipants. Initially, proposals for improvement are given on three levels; government, employer, and society. The main improvement should be the better flow of infor- mation, for which we suggest transferringmore information online. Slovene society should be striving for tolerance so that foreigners would feel more welcomed.
Keywords: imigranti; tourism; turizem; zaposleni; zaposlovanje